The Development of Social Media Trends in Public Participation: A Bibliometric Visualization Using VOSViewer - Randisa, Aziz Reza; Asriadi, Asriadi; Sari, Inrinofita (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This The purpose of this study is to analyze the development of social media trends in public participation. The research data is 427 Scopus documents from the last five years, 2021-2025. This research method uses a qualitative approach with a bibliometric analysis. The research data analysis uses VOSViewer software to visualize the data by auto-coding. The findings of this study indicate that social media trends focus on issue sentiment, tweets, surveys, and citizens, which are widely used to convey criticism and fast messages to the state. Furthermore, governments in developed countries also use social media as a space to convey information and public communication. The United States (42%) is the country that focuses most significantly on developing innovation in its social media trends. Male users dominate social media trends in developed countries on Reddit (68%), while female users are dominated by Facebook (60%). Meanwhile, Instagram (59%) is the second most used by women. Media X (Twitter) also ranks second (64%) and is widely used by men. However, based on the age group 18-29, TikTok dominates (45%), Reddit dominates (46%) for those aged 30-49, YouTube dominates (23%), and YouTube dominates (16%). The implications of this research indicate that the existence of social media is a crucial part of the rapid development of Artificial Intelligence, so its existence cannot be ignored. Keywords: Development, Trends, Social Media, Public Participation